Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Melipat Kertas Di Kelompok A Tk Harapan Bangsa Jono Oge Kecamatan Sigi Biromaru - Sumiarti, Evi (Bungamputi, 2013)
ABSTRACT Â The aim of this research is to improve the study process to affect at the result of learning. The background of problem is caused by less maximal study, so that the ability of child motorik is less expanding. The method used is research of class action becoming its subject is group child of A Harapan Bangsa Kindergarten Jono Oge District of Sigi Biromaru amounting to 20 children. Consist of 9 daughters and 11 boys. Collected data using the observation sheet and also giving of duty and documentation, after that itâ€™s analyzed with descriptively qualitative technically percentage to take conclusion. Result of this research can be concluded that skill fold paper can improve growth of child motorik in group of Harapan Bangsa Kindergarten Jono Oge District of Sigi Biromaru proven there is make-up growth of smooth motorik of child at first cycle category very good and good 41,25% and the second cycle mountong to become 81,25% of mount 40%, although there are children still not yet succeeded 18,75%. Â Kata Kunci : Kemampuan Motorik Halus dan Kegiatan Melipat Kertas